Catalysis for a sustainable world - Yap, Taufiq Yun Hin (Universiti Putra Malaysia Press, 2009)
Future global prosperity will depend on new or improved processes that are economically and environmentally sustainable. This is the paradigm shift of the early 21st century, driven by the threat of climate change and the increasing scarcity of raw materials. Catalysis has a leading role in many chemistry solutions, as the key enabling science in some cases, and as part of general technology in others. Catalysts are used widely within chemical production, power production, refinery processes, conversion of natural gasses, chiral synthesis, agro chemistry, pharmaceutical processes, polymer and material production and biotechnology. The economic impact of catalysis is perhaps best illustrated by the fact that in the industrialized world heterogeneous catalysis is involved in 20-25% of the gross national products. Many of the major problems society is encountering, such as the need to create production in balance with the environment, better use of fuels, more economical energy production and the reduction of CO2 and other green house gasses, will require solutions where catalysts play an important role. Furthermore, the development of new catalysts and catalytic processes can open up new selective chemical processes which may lead to a considerable reduction of undesired by-products or waste products. Selective catalytic oxidation is one of the major areas in industrial chemical production. Vanadium phosphate catalyst is one of the most extensively used catalysts for several mild oxidation of hydrocarbons. Another example of catalytic technology development is the use of heterogeneous catalysts for promoting transesterification for the production of green biodiesel. Due to the high energy demand both in industrialized world and domestic sectors, and the pollution problems caused by the use of fossil fuels, it is necessary to develop a limitless duration with smaller environmental impact of renewable energy sources. A lower cost of biodiesel can be obtained by using heterogeneous catalysts with higher quality of esters and glycerol.